Approaches and Limitations of L2 Textbook Evaluation Research - Kalfut, Thamer (International Journal of Language and Literary Studies, 2024)
The evaluation of L2 textbooks is an important aspect of curriculum development in L2 learning and teaching. It has been the subject of research since the 1970s. A large number of studies have been conducted to investigate the language skills, linguistic elements, or/and social factors presented in textbooks. However, even so, the issue of evaluation research approaches has not received very much critical attention. As a result, this research project is concerned with the methodology used in textbook research. It aims to provide an overview of current approaches to L2 textbook evaluation research, as well to highlight their major limitations. It reviews research methods used in previous studies targeting textbooks from grade one to grade twelve in various countries and reveals two main approaches. The first approach seeks to conduct a thorough assessment of one specific English textbook. L2 material researchers often use a Likert scale checklist to investigate the strengths and weaknesses of an entire English language textbook. The second approach evaluates an English textbook from a micro perspective, with a particular emphasis on one single aspect of it, such as reading or writing. These findings may help us to better understand current evaluation approaches used by textbook researchers and their limitations. It shows what needs to be done to improve this evaluation process in the future.